Analisis Jejaring Sosial sebagai Bentuk Diplomasi Digital Indonesia dengan Negara Kawasan Eropa Timur - Anti Prasasti (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
This research aims to analyze the pattern of Indonesian diplomacy with countries in the Eastern European region using a quantitative approach and Social Network Analysis methods. In this research data collection uses the Twitter Developer API tools which are then processed using Gephi 0.9.2 and Microsoft Excel tools. In today's digital era, communication between actors can not only be done through physical meetings. The impact of these technological and communication developments has provided a shift in the implementation of diplomacy between countries. This encourages each country to make adaptations in improving its diplomatic relations. As one of the steps to face the technological and communication revolution, diplomacy between countries is established through digital diplomacy. Digital diplomacy is a diplomatic activity that is carried out using digital instruments, in this case, social media.